Extinction risk analysis of Anthocephalus macrophyllus in Gunungsewu Karst Area, Southern Java, Indonesia - LIES RAHAYU WIJAYANTI FAIDA; HERO MARHAENTO (Society for Indonesian Biodiversity, 2019)
Abstract. Faida LRW, Marhaento H. 2019. Extinction risk analysis of Anthocephalus macrophyllus in Gunungsewu Karst Area, Southern Java, Indonesia. Biodiversitas 20: 1897-1903. This paper aims to analyze the extinction risk of a local plant species namely Tebelo Pusoh or Jabon Merah (Anthocephalus macrophyllus) in Gunungsewu Karst Area (GKA), Southern Java, Indonesia. A. macrophyllus is a native species of GKA which its existence is currently being threatened by anthropogenic activities such as agricultural extension and housing development. To quantify the extinction risk of A. macrophyllus in GKA, an adapted equation from International Institute of Rural Reconstruction (IIRR) was used. Three extinction risk components namely hazard, vulnerability and coping capacity were assessed based on the local’s perception. Hazard was defined as a source of potential threat to A. macrophyllus, vulnerability was a state of A. macrophyllus being exposed to damage, and coping capacity was efforts to reduce the potential damage of A. macrophyllus. Interviews with one hundred and ten respondents were conducted to assess the risk components. The Likert scale was used to analyze the interview results. The results showed that within the scale of 1 to 4, the hazard score for A. macrophyllus was 2.67, the vulnerability score was 1.67, and the coping capacity score was 1.33. Finally, it was estimated that the extinction risk of A. macrophyllus in GKA was 3.35 indicating a moderate level of extinction risk.